A Molecular Insight into the Dehydration of a Metal–Organic Framework and its Impact on the CO2 Capture. Issue 18 (24th February 2023) - Lian, Jian Xiang; Siahrostami, Samira
Abstract: Metal–organic frameworks (MOFs) are porous material formed by the self‐assembly of metallic ligands and organic linkers. They are a good candidate for CO2 gas capture because they have large surface areas and the metal or linker can be tuned to improve CO2 uptake. In the quest for water and acid stable MOFs, a phosphonate‐based organic linker has recently been designed by Glavinovic et al. ( Chem. Eur. J . 2022, 28, e202200874). By combining ionic calcium nodes, water and methanol molecules, they formed a microporous network, CALF‐37. This network has been shown to be robust and can maintain its pore shape even in absence of water molecules or by the inclusion of gas molecules, such as CO2 . The network can be heated to release the water and methanol molecules and form a dehydrated MOF, which retains its shape with the imprinted pore within. Herein, we perform molecular dynamics (MD) simulations in order to provide insight into the CO2 capture and sequestration ability of the CALF‐37. We model the dehydration of the inactivated MOF (HCALF‐37) in the absence and in the presence of methanol molecules by progressively withdrawing water molecules from the MOF networks. We determine the crystal structure of the intermediate states from HCALF‐37 to CALF‐37 and shed light on the critical role of water molecules in the mediation of metal‐linker bonds. Our calculations also reveal that the favorable interactions between the CO2 molecules and the aromatic core of the linkers and metallic ions are responsible for the efficient sequestration of the gas in the CALF‐37. Abstract : MD simulations were used to investigate the reasons for CALF‐37′s resistance to water, as well as its uptake capacity and selectivity to CO2 vs. N2 .